Treatment of Autoimmune Bullous Diseases During Pregnancy and Lactation: A Review Focusing on Pemphigus and Pemphigoid Gestationis - Genovese, Giovanni; Derlino, Federica; Berti, Emilio; Marzano, Angelo Valerio (Frontiers in Pharmacology, 2020)
Pregnancy may induce the onset or exacerbation of autoimmune bullous diseases such as pemphigus or pemphigoid gestationis. A shift toward T helper (Th) 2 immune response and the influence of hormonal changes have been evoked as possible triggering factors. Therapeutic management of this setting of patients may represent a challenge, mainly due to safety concerns of some immunosuppressive drugs during pregnancy and lactation. In this narrative review, we provided a comprehensive overview of the therapeutic management of autoimmune bullous diseases in pregnant and breastfeeding women, focusing on pemphigus and pemphigoid gestationis.